Mistisisme Ekstraversif dalam Teks Panugrahan Dalem - Harsananda, Hari (Institut Hindu Dharma Negeri Denpasar, 2021)
Religion is a means for humans to connect with God, this relationship is full of mysticism, both introversive mysticism and extraversive mysticism. The Panugrahan Dalem text is one of the literary texts that contains the teachings of extraversive mysticism, namely the teachings of mysticism